First, use these rules of exponents to simplify the numerator:
x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b)) and a^color(red)(0) = 1
(120^color(red)(-2/5) * 120^color(blue)(2/5))/7^(-3/4) => 120^(color(red)(-2/5)+color(blue)(2/5))/7^(-3/4) =>
120^color(red)(0)/7^(-3/4) => 1/7^(-3/4)
Next, we will use this rule to rewrite the expression:
1/x^color(red)(a) = x^color(red)(-a)
1/7^color(red)(-3/4) = 7^color(red)(- -3/4) = 7^(3/4)
Then, we can rewrite the expression as:
7^(3 xx 1/4)
Now, we can use this rule of exponents to continue the simplification:
x^(color(red)(a) xx color(blue)(b)) = (x^color(red)(a))^color(blue)(b)
7^(color(red)(3) xx color(blue)(1/4)) => (7^color(red)(3))^color(blue)(1/4) => 343^(1/4)
Or, using this rule: x^(1/color(red)(n)) = root(color(red)(n))(x)
root(4)(343)